Rifampicin-induced thrombocytopenia in a patient of disseminated tuberculosis (Indian Journal of Case Reports, 2022)
Thrombocytopenia may be associated with a variety of conditions and risks depending on its severity, ranging from mild epistaxis to life-threatening bleeding. Many drugs or herbal remedies can cause thrombocytopenia by either inhibiting platelet production and/or enhancing their destruction from the peripheral blood-mediated through an immunological mechanism implicating drug-dependent antibodies. Drugs are a common cause of acute immune-mediated thrombocytopenia in adults, the drug etiology is often initially unrecognized. Most cases of drug-induced thrombocytopenia are caused by drug-dependent antibodies that are specific for the drug structure and bind tightly to platelets by their Fab regions but only in the presence of the drug. Thrombocytopenia is an uncommon but life-threatening complication of certain antitubercular drugs. The discovery of isolated thrombocytopenia in a patient taking several medications presents a challenging clinical problem. We report a case of a young immunocompetent female who presented with disseminated tuberculosis and was found to have rifampicin-induced thrombocytopenia.